Pelanggaran Hak Asasi Terhadap Kelompok Masyarakat Adat Dalam Konflik Agraria Dan Peranan Pemerintah Dalam Penyelesaianya - Iskandar, Iskandar; Azis, Husni Abdul (Jurnal Hukum In Concreto, 2023)
The Kinipan indigenous people often become victims of crime, where natural resources and conversion of the function of the Kinipan indigenous people's forests have disrupted the sustainability and fundamental interests of the community. What happened in the Kinipan customary land contradicts Article 18B paragraph (2) and Article 281 paragraph (3) of the 1945 Constitution. This study aims to identify and analyze the state's responsibility in protecting its citizens, especially in fulfilling agrarian rights as a constitutional right. The research method used is descriptive analysis with a normative juridical approach; data collection techniques are carried out using library data. Based on the study's results, it was found that arrangements regarding the rights and whereabouts of the community have been regulated in the constitution and various laws and regulations in Indonesia, but more than these regulations is needed to protect and meet the needs of indigenous peoples. The state's responsibility for the conflict is that the government provides what the Kipan community needs.